Urological Cancers - Waxman, Jonathan (Springer London : Imprint: Springer, 2005)
Our understanding of the scientific basis for urothelial malignancy has advanced significantly. Studies in prostate cancer, few and far between 20 years ago, have increased and the degree of Government intervention, both in Europe and America, to support work in this field has risen considerably. Interest within the pharmaceutical industry has grown as well, and this has led to the development of new treatment options for all of the urological malignancies and real improvements in remission rates and durations. This book outlines developments in all areas of urological cancer, bringing together, in one volume, summaries of clinical and molecular advances, which will be invaluable to urologists and oncologists.